VULNERABILITIES TRANSPOSED BY CLIMATE CHANGE EFFECTS IN ECOLOGICAL RISKS AND THREATS TO THE NATIONAL SECURITY - ATANASIU, Mirela (Strategic Impact, 2024)
Climate changes effects determine major transformations of interactions between socio-economic and natural environment, phenomena that directly affect the overall security (international, national, regional) systems. In the security equation, vulnerabilities in different sectors expose systems to threats and associated risks and their existence represents gaps and malfunctions in assuring systems’ overall resilience. In this paper, we start from the research hypothesis that vulnerabilities are a constitutive element of the climate security equation seen as a logical construction of a causal nature, respectively: the effects of climate changes are the source of ecological threats and associated risks facilitated or multiplied by exploited vulnerabilities whose presence/absence gives the measure of the impact over the respective security system. In this regard, our topic is focused on a narrower subject, namely the identification of vulnerabilities that have the potential to be exploited in generating ecological threats and associated risks against Romanian national security. In order to achieve our goal, concepts like “environmental security”, “climate security”, “ecology”, “climate change”, “vulnerability”, “ecological risks and threats”, and “resilience” will be approached in the capacity of their interdisciplinary entanglement between security and ecology.